Predicting Relationship Between Anxiety and School Avoidance in Children and Adolescents with and Without Learning Disabilities in Educational Setups in Pakistan: A Comparative Study (Journal of Education and Educational Development, 2023)
This study aimed to investigate anxiety and school avoidance in individuals with and without learning disabilities. The study employed quantitative survey-based approach, with comparative research design. N= 160 participants between 8 till 18 years were selected via Purposive sampling technique. Screen for Child Anxiety Related Disorders (Birmaher et al., 1999) was administered to measure anxiety and school avoidance and Learning Disabilities Checklist (National Centre for Learning Disabilities, 2007) was used to assess learning disabilities in participants. Data was analyzed using Statistical Package for the Social Sciences (SPSS) version 22. Results were analyzed using descriptive and inferential statistics. Correlation and regression analysis were done to study the relationship and level of variance between the variables. Results indicated significant differences on the variable of anxiety (t=-3.95, df =140.71, p
Keywords: anxiety disorder; learning disabilities; school avoidance; children; adolescent